Economic burden of inpatient and outpatient antibiotic treatment for methicillin-resistant Staphylococcus aureus complicated skin and soft-tissue infections: a comparison of linezolid, vancomycin, and daptomycin - Stephens JM; Gao X; Patel DA; Verheggen BG; Shelbaya A; Haider S (Dove Medical Press, 2013)
Jennifer M Stephens,1 Xin Gao,1 Dipen A Patel,1 Bram G Verheggen,2 Ahmed Shelbaya,3,5 Seema Haider4 1Pharmerit North America, Bethesda, MD, USA; 2Pharmerit Europe, Rotterdam, The Netherlands; 3Pfizer Inc, New York, NY, USA; 4Pfizer Inc, Groton, CT, USA; 5Mailman School of Public Health, Columbia University, NY, USA Background: Previous economic analyses evaluating treatment of methicillin-resistant Staphylococcus aureus (MRSA) complicated skin and soft-tissue infections (cSSTI) failed to include all direct treatment costs such as outpatient parenteral antibiotic therapy (OPAT). Our objective was to develop an economic model from a US payer perspective that includes all direct inpatient and outpatient costs incurred by patients with MRSA cSSTI receiving linezolid, vancomycin, or daptomycin. Methods: A 4-week decision model was developed for this economic analysis. Published literature and database analyses with validation by experts provided clinical, resource use, and cost inputs on data such as efficacy rate, length of stay, adverse events, and OPAT services. Base-case analysis assumed equal efficacy and equal length of stay for treatments. We conducted several sensitivity analyses where assumptions on resource use or efficacy were varied. Costs were reported in year-end 2011 US dollars. Results: Total treatment costs in the base-case were lower for linezolid ($10,571) than vancomycin ($11,096), and daptomycin ($13,612). Inpatient treatment costs were $740 more, but outpatient costs, $1,266 less with linezolid than vancomycin therapy due to a switch to oral linezolid when the patient was discharged. Compared with daptomycin, both inpatient and outpatient treatment costs were lower with linezolid by $87 and $2,954 respectively. In sensitivity analyses, linezolid had lower costs compared with vancomycin and daptomycin when using differential length of stay data from a clinical trial, and using success rates from a meta-analysis. In a scenario without peripherally inserted central catheter line costs, linezolid became slightly more expensive than vancomycin (by $285), but remained less costly than daptomycin (by $2,316). Conclusion: Outpatient costs of managing MRSA cSSTI may be reduced by 30%–50% with oral linezolid compared with vancomycin or daptomycin. Results from this analysis support potential economic benefit and cost savings of using linezolid versus traditional OPAT when total inpatient and outpatient medical costs are evaluated. Keywords: economic model, OPAT, cost